Double-J stents forgotten for four years: a case report (Faculty of Medicine Universitas Indonesia, 2019)
Placement of double-J ureteral stents after endourologic procedures and some open urological surgeries are practical and safe. However, when neglected in situ, undesired problems may occur, leading to serious medical and legal issues. Complications from ureteral stents with protracted indwelling durations include urosepsis, renal failure, encrustation, and spontaneous fractures which may be retained or voided in the urine (stenturia). We report a 40-year-old woman of forgotten double-J ureteral stents, inserted 4 years prior to this study during a gynecologic operation. The patient had pulled out the double-J stents from her urethra herself and presented with impending sepsis. Then, she underwent ureterorenoscopic lithotripsy, but it failed to remove the remaining encrusted double-J stent. As a result, percutaneous nephrolithotomy was performed successfully and she had symptom-free thereafter.